ANALISA PENGARUH FREE CASH FLOW, AUDIT INTERNAL, LIKUIDITAS, LEVERAGE DENGAN DISCREATIONARY ACCRUAL Pada PT. ALSY - Martias, Andi (www.bsi.ac.id, 2020)
Abstract - Discreationary accruals as a representative in earnings management calculation parameters. The theory in which calculated by excluding total accruals with non-discreationary accruals. This model uses Total Accrual (TA) which is classified into discreationary accrual (DA) and non discreationary accrual (NDA). This research process aims to determine the process of managing management responsibilities for financial reporting for shareholders there is no miss information. The earnings management method is part of the accounting method used in financial reporting for investors.The analysis used in this study is to see the extent of the influence of free cash flow, internal audit, liquidity ratios, leverage ratio to discreationary accrualrs as representatives of earnings management. Measurement with the ratio approach and the results of the company's internal audit process. The research sample service companies in the field of loss insurance which are listed on the Indonesia stock exchange quarter 1 to quarter 4 during the period 2015 - 2018. Regression panel data is used to test hypotheses. Hypothesis results found no significant correlation between free cash flow, liquidity and leverage with discreationary accruals. Internal audit and free cash flow affect discretionary accruals with a confidence level of 90%, meaning a standard error of 10%. Whereas leverage and liquidity do not have impact with discretionary accruals. This means thus the performance of both there is no correlation to earnings management in the practice of the company under study. Keywords: free cash flow, liquidity ratio, leverage ratio, internal audit, discreationary accruals